The Auditory brainstem response latencies in children with global developmental delay at Dr. Cipto Mangunkusumo Hospital - Muhammad Ade Rahman; Tri Juda Airlangga; Fikry Hamdan Yasin; Rini Sekartini; Achmad Rafli; Ferdi Afian (PERHATI-KL, 2026)
Background: Global developmental delay (GDD) affects multiple developmental domains and remains a major concern in early childhood. The auditory system plays a key role in language development, and the Auditory Brainstem Response (ABR) test provides an objective measure of auditory pathway maturation. However, data on ABR wave latencies among children with GDD who have normal predicted hearing thresholds are limited. Purpose: To describe absolute and interwave latencies of ABR waves I, III, and V, and to compare latencies of ABR waves across demographic and perinatal clinical characteristics in children with GDD. Method: A cross-sectional analytical study was conducted using medical record data from 70 children aged 6 months to 5 years with GDD at Dr. Cipto Mangunkusumo Hospital between January 2021 and May 2025. All subjects had normal predicted hearing thresholds (≤30dB) in ABR result and passed Distortion Product Otoacoustic Emission (DPOAE) screening. Comparations between risk factors (age, gender, gestational age, birth weight, NICU admission, asphyxia, and hyperbilirubinemia) and ABR latencies were analyzed using t-test or Mann–Whitney test. Result: Most subjects were male (71.4%) with a median age of 25 months. The language domain was most frequently affected (92.9%). Male subjects had a significantly longer absolute latency of wave V in the left ear compared to females (6.10±0.31 ms; p < 0.05). Conclusion: Male gender with normal predicted hearing threshold had significant difference in the left-ear wave V latency compared to female. ABR is a valuable tool for early detection of auditory pathway maturation delay in at-risk children.